Pengembangan Aplikasi Text-to-Speech Bahasa Indonesia Menggunakan Metode Finite State Automata Berbasis Android - Rieke Adriati W.; Herman Tolle; Onny Setyawati (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2016)
In this paper, the development of Android-based Indonesian Text-to-Speech (TTS) utilizing API Google for English TTS as a data voice has been proposed. Using this approach, a lightweight and mobile Indonesian TTS application can be realized. The utilization of English data voice is carried out by cutting off (hyphenate) Indonesian words into syllables using Finite State Automata method, then searching for equivalent syllables in English which have similar pronunciation. Using FSA method, this system is able to hyphenate all Indonesian words up to 95.19%. This application has Mean Opinion Score (MOS) value of understanding the words criteria of 3.31 and MOS value of smoothness pronunciation criteria of 3.46 (in a scale of 5).